Increasing knowledge in healthy lifestyle of nutrition education in Samarinda Senior High Schools - Wisnuwardani, Ratih Wirapuspita; K, Iriyani; Nurzihan, Nastitie Cinintya; Susanto, Riezfian Raditya; Afiah, Nurul (Journal of Community Empowerment for Health, 2024)
Introduction: Nutrition education is crucial in promoting a healthy lifestyle, including nutritious food consumption, to prevent anemia and stunting in Samarinda, East Kalimantan. The teenage years represent a crucial phase characterized by significant physical and psychological maturation, essential for optimal growth and development. Within this period, adolescents have distinct physiological and psychological requirements. Furthermore, nutritional deficiencies during this time can pose significant health challenges. This study evaluated the association between nutrition education and knowledge of healthy behaviors in Samarinda adolescents. Methods: This study used an action study among 59 high school students (10% overweight, 15-18 years) in Samarinda. Three meetings at every school, with pre-test, nutrition education, Kahoot game, and post-test. All participants were given information regarding the benefits and risks of the program before participation and signed an informed consent. A questionnaire measured knowledge of balanced nutrition, MyPlate contents, and physical activity. Paired t-test was used for the statistical analysis. Results:The majority of participants were female (80%), had normal nutritional status (63%), and did not regularly consume iron tablets (95%). Most participants knew about anemia from their parents (88%), so they suggested nutrition education such as anemia through face-to-face training and social media. An improvement in knowledge before and after face-to-face nutritional education was found in this study (p<0.001)Conclusion: There is an effect of providing education to increase knowledge in nutrition education among adolescents.